Case study of indoor air quality of health care facilities and hospitals in Malaysia / Phuah Kok Sun - Phuah, Kok Sun (2012)
Hospitals and healthcare facilities are buildings that require proper design for diverse environment due to their nature. The comfort of occupants and the spread of germs should be consider in the design of such facilities. Airborne diseases have become a serious concern after the spread of influenza H1N1 and Severe Acture Respiratory Syndrome (SARS) viruses. Healthcare facilities, particularly those built in the past, do not consider air as the transport medium for infectious diseases. Most of the recent studies in indoor air control revolve around specialized environments such as isolation rooms and operating theatres. This dissertation studies the indoor air quality (IAQ) of different hospitals for tropical climate. Standard procedures extracted from ASHRAE standards are applied in the fieldwork to obtain accurate objective measurements and subjective assessments. The objective measurements include measurements of temperature, relative humidity, air velocity, formaldehyde (HCOH), carbon dioxide (CO2), carbon monoxide (CO), total volatile organic compounds (TVOCs), particulate matter (PM) and biological pollutants. For subjective assessment, questionnaires and interviews are conducted to study the background of occupants within the building. Air distributions are simulated with the aid of a CFD tool to support the findings for indoor air quality investigations in healthcare facilities. The research is divided into four main categories. The first study involves investigating the effect of internal design for air-conditioning mechanical ventilation (ACMV) system on the air distribution and IAQ for a pharmaceutical laboratory. The second study investigates the IAQ profile of a pre-occupied hospital. The third study focuses on the IAQ and thermal comfort between centralized and non-centralized ACMV systems. Finally, the fourth study examining the use of tea tree oil as a decontamination agent for biological pollutants in humid climates. The results show that modifications on the ACMV internal design such as location of the diffuser and exhaust are significantly related to the utilization of the room. The diffuser can be used to control and provide a clean work surface for chemical testing in the pharmaceutical laboratory. However, these criteria must be accompanied by proper maintenance of the ventilation system. IAQ audits in hospitals reveal that more occupants under the centralized ACMV systems feel uncomfortable compared to the non-centralized ACMV systems. This indicates that occupants prefer higher temperature and humidity compared with the ASHRAE Standard-55, which promotes energy savings. However, centralized ACMV hospitals exhibit better indoor air quality control for chemical and particulate contaminants. Measurements in all healthcare buildings exhibit a high relative humidity beyond the threshold set by ASHRAE. Humid environment favours the growth of contaminants and colonization of microorganisms, which will accumulate within the facility, especially at the edges of the workspace. Vapourised tea tree oil is sprayed throughout the air-conditioning space via Air-handling Unit (AHU), and the survival of microbial pollutants such as bacteria, fungi and mould is successfully reduced to acceptable levels. Hence, tea tree oil is a potential decontamination agent for air treatment besides the common agent (i.e. hydrogen peroxide). This study shows that indoor environment in Malaysian healthcare facilities still have areas for improvement.